The Message of II Peter & Jude:the promise of His coming - Lucas, Dick (Leicester Inter-Varsity Press, 1995)
The message of 2 Peter and Jude. The promise of his coming. An exposition of two letters which set forward Christian growth as the church's remedy against the destabilising force of heretical teaching and false guides.
Keywords: Second Advent. Bible. -- New Testament. -- Catholic Epistles -- Criticism, interpretation, etc. II Petrus (bijbelboek)